Dressing effects in the attosecond transient absorption spectra of doubly excited states in helium - Argenti, L.; Jiménez-Galán, Á.; Marante, C.; Ott, Christian; Pfeifer, Thomas; Martín, F. (Physical review. A, Atomic, molecular, and optical physics, 2015)
Strong-field manipulation of autoionizing states is a crucial aspect of electronic quantum control. Recent measurements of the attosecond transient absorption spectrum (ATAS) of helium dressed by a few-cycle visible pulse [C. Ott et al., Nature (London) 516, 374 (2014)] provide evidence of the inversion of Fano profiles. With the support of accurate ab initio calculations that reproduce the results of the latter experiment, here we investigate the new physics that arise from ATAS when the laser intensity is increased. In particular, we show that (i) previously unnoticed signatures of the dark 2p21S doubly excited state are observed in the experimental spectrum, (ii) inversion of Fano profiles is predicted to be periodic in the laser intensity, and (iii) the ac Stark shift of the higher terms in the sp+2,n autoionizing series exceeds the ponderomotive energy, which is the result of a genuine two-electron contribution to the polarization of the excited atom.